2002
DOI: 10.1590/s1415-47572002000300002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct nonrandom patterns of chromosomal deletions in giant-cell lesions of bone

Abstract: Cytogenetic analyses were performed on a bone giant cell reparative granuloma (GCRG) and on three bone giant cell tumors (GCT). The present GCRG case is the second to be described cytogenetically. A modal chromosome number of 46 was observed in all samples. Clonal chromosome abnormalities were detected in all cases. The numerical alterations most frequently observed involved the loss of chromosomes 17 and 18. Among the structural anomalies observed, there was preferential involvement of chromosomes 6 and 10. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several reports concerning bone/cartilage-forming lesions or benign mesenchymal tumours have demonstrated associations with changes on 6q and 12q [1,2]. In addition, gains on 1q, 6q and 12q have been associated with a subgroup of malignant bone fibrous histiocytoma of undifferentiated status, suggesting a possible role of these genomic alterations in GCT [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports concerning bone/cartilage-forming lesions or benign mesenchymal tumours have demonstrated associations with changes on 6q and 12q [1,2]. In addition, gains on 1q, 6q and 12q have been associated with a subgroup of malignant bone fibrous histiocytoma of undifferentiated status, suggesting a possible role of these genomic alterations in GCT [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Baruffi et al (2002) reported deletions involving 10p13-pter in three cases of giant-cell bone lesions. There are 66 genes or hypothetical genes mapped to this region (http://cgap.nci.nih.gov/Genes/GeneFinder), including DNMT2 (DNA cytosine-5-methyltransferase 2), located at 10p15.1.…”
Section: Using Interphase Fish We Demonstrated the Presence Of Cgh Amentioning
confidence: 99%